1982
DOI: 10.1016/0304-4165(82)90230-6
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentation of hexokinase in human blood cells characterization of soluble and particulate enzymes

Abstract: The isozyme distribution, kinetic properties and intracellular localization of hexokinase (ADP: l>hexose-6-phosphotransferase, EC 2.7.1.1) were studied in erythrocytes, blood platelets, lymphocytes and granulocytes. Soluble and particulate fractions were separated by a rapid density centrifugation method after controlled digitonin-induced cell lysis. In lymphocytes and platelets the major part of total activity was particle-bound (78 and 88%, respectively). In granulocytes and erythrocytes most of the hexokina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Confocal microscopic analysis confirmed that membrane-associated GLUT1 was similar between HD and GSD-Ib neutrophils ( Figure 2E). The expression of HK1 mRNA is downregulated and HK2 is unchanged, but the expression of HK3, the major HK isozyme in neutrophils, 35,36 BLOOD, 1 MAY 2014 x VOLUME 123, NUMBER 18 …”
Section: Resultsmentioning
confidence: 99%
“…Confocal microscopic analysis confirmed that membrane-associated GLUT1 was similar between HD and GSD-Ib neutrophils ( Figure 2E). The expression of HK1 mRNA is downregulated and HK2 is unchanged, but the expression of HK3, the major HK isozyme in neutrophils, 35,36 BLOOD, 1 MAY 2014 x VOLUME 123, NUMBER 18 …”
Section: Resultsmentioning
confidence: 99%
“…An analogous situation exists for the enzyme hexokinase, which binds to a proteinaceous binding site in the membrane of mitochondria. This enzyme is more resistant to digitonin solubilization than adenylate kinase, an enzyme whose liberation depends only on the permeabilization of the mitochondrial membrane (20,21). (iii) The third compartment is the chromaffmi granule, which is relatively insensitive to digitonin permeabilization (16,17) and therefore retains intragranular components such as dopamine 3-hydroxylase and catecholamines.…”
Section: Resultsmentioning
confidence: 99%
“…The plasma membrane of isolated chromaffin cells becomes leaky to proteins and small molecules, while the chromaffin granule membrane is unaffected and the calcium-sensitive secretory machinery remains relatively intact (16,17). Digitonin has been used to investigate the subcellular distribution of many small molecules and proteins (18)(19)(20)(21)(22)(23) Lactate dehydrogenase was measured by monitoring the formation of NADH from NAD. Aliquots (100 ,ul of cell lysate or digitonin medium) were incubated with 60 mM lactate/100 mM Tris, pH 9.0/1 mM NAD in a final vol of 1.1 ml at room temperature for 30 min.…”
mentioning
confidence: 99%
“…14,15 In particular, HK3 is the major hexokinase member present in granulocytes (70%-80% of total activity), with the remaining 20% to 30% of the activity provided by HK1. 16 Here we describe that HK3 is significantly down-regulated in primary APL, and its expression is restored on ATRA therapy. We further identified HK3 as direct transcriptional target of PU.1 and PML-RARA.…”
Section: Introductionmentioning
confidence: 96%